(untitled) (Archives of Criminology, 2023)
The countries of Central Europe have for many years occupied a leading position in Europe when it comes to the level of incarceration. This begs the question of what lies behind this state of affairs. It may be connected with the history of the region, being under authoritarian rule for years. Another factor may be the penal populism that is present everywhere in the world, but has specific features in this region. One version of such explanations is the concept of “penal nationalism”. The research also indicates a relationship between social policy and egalitarianism, among other factors, and the size of the prison population. This raises the question of the extent to which the concepts relativizing punitiveness to categories of political economy apply to the region. Finally, there are other explanations that point to some prosaic factors of a “technical” nature that may have an undesirable influence on punitiveness. None of these concepts fully explain the unique situation of the region as a whole. However, they can be a starting point for building a more integrated concept.